Effects of pH of TEOS solution on morphology, thermal stability and mechanical properties of EVA/silica nanocomposites prepared by sol-gel method - Quang Tham, Do; Hoang, Thai; Thuy Chinh, Nguyen (Vietnam Journal of Science and Technology, 2017)
Ethylene-vinyl acetate copolymer/silica nanocomposites (EVA/silica) were prepared by mixing EVA solutions and tetraethylorthosilicate (TEOS) solutions. Silica particles were formed through sol-gel mechanism with the aid of hydrochloric acid catalyst and dispersed in EVA matrix. The pH of TEOS solutions was controlled from 1 to 6. The influence of pH on formation of silica in EVA matrix, as well as morphology, thermal stability of the nanocomposites were characterized by using Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and field emission scanning electron microscopy (FESEM). The FTIR spectra of the nanocomposites clearly indicated the presence of silica in EVA matrix, the shifts of Si-O stretching vibration in the nanocomposites in comparison with pure silica were also observed. This can be explained by hydrogen bonding between SiOH groups of the silica and carbonyl groups of vinyl acetate units in EVA. The TGA results of the nanocomposites showed that silica could improve thermal stability of EVA. Comparing preparation conditions at pH from 1 to 4, it is clear that at the lower pH the higher content of silica was formed in EVA matrix, 3.78; 3.70; 2.50 and 2.09 wt.% respectively. The FESEM images of the nanocomposites showed that nanoscale dispersion of silica was observed obviously at pH of 4 - 6, whereas during their preparation at pH of 1 - 3, the obtained silica particles formed mainly in microscale. The pH also affected on the mechanical properties (tensile strength, elongation at break) of EVA/silica nanocomposites. At pH of 1 - 3, the silica particles formed mainly in larger size, thereby they reduced the mechanical properties of EVA. At pH of 4 - 6, the nanosilica particles had significantly improved mechanical properties of EVA, particularly at pH of 4. The improvement of shear modulus of EVA/silica was also discussed.